Hakikat Pembelajaran dalam Perspektif Pendidikan Islam: Kajian Konseptual dan Pedagogis - Ikat Sutriani; Novita Eni Kartika; Imam Syafe'i; Eti Hadiati; Ratu Vina Rahmatika (Paedagogie, 2026)
Learning constitutes the core of the educational process aimed at developing students’ potential in a comprehensive manner. In the perspective of Islamic education, learning is not merely understood as a process of knowledge transmission, but also as a process of cultivating values, moral character, and spiritual awareness. This study aims to analyze the essence of learning from the perspective of Islamic education through a conceptual and pedagogical approach. The research employs a qualitative approach using a library research method. The data were obtained from various academic sources, including books and scholarly journal articles relevant to the research topic. Data collection was conducted through documentation studies, while data analysis employed descriptive-analytical methods to systematically examine the concept of learning within Islamic education. The findings reveal that learning in Islamic education possesses an integrative character that combines cognitive, affective, and psychomotor dimensions. Learning is not solely intended to develop students’ intellectual abilities, but also to instill moral and spiritual values as the foundation for character formation. Therefore, learning in the perspective of Islamic education emphasizes the balance between the development of knowledge and the cultivation of moral character, aiming to produce individuals who are knowledgeable, faithful, and possess noble character.